(untitled) (Indonesian Sports Justice Review, 2025)
Doping remains a significant challenge in Indonesian sports, undermining fairness, integrity, and the pursuit of justice in competitive environments. This paper examines the legal frameworks and ethical dilemmas surrounding doping in Indonesian sports, focusing on the effectiveness of anti-doping laws and the impact of doping on athlete rights and competition integrity. The study provides an overview of high-profile doping cases in Indonesian sports, analyzing how these incidents affect public perceptions, athlete careers, and the broader sports community. The paper also explores the tension between maintaining strict anti-doping policies and protecting athlete autonomy. Recommendations are made for improving legal enforcement, athlete education, and the ethical standards governing doping in Indonesian sports to promote a more just and equitable playing field.